Evaluation of Epistemic Beliefs Self-Report Questionnaires in the Czech Middle School History Classroom - Jaroslav Říčan; Ondřej Pešout (Charles University, 2023)
Epistemic beliefs are gaining increasing importance in social science education in Czechia. Recent literature has demonstrated findings linking epistemic beliefs with various academic skills, including achievement and reading comprehension. The present study aims to explore the epistemic beliefs of adolescents specific to the domain of history. The study reviews research literature on ontological changes in students' epistemic beliefs and their reasoning within the domain of history since the 1950s, with a particular focus on various models and measurement. The empirical part of the study investigates adapted self-report questionnaires on the epistemic beliefs of adolescents in Czech history classes in the upper grades of middle school. In the first step, the selected questionnaires were back-translated and refined by iterative sets of cognitive interviews. The finalised sets of items were administered in seventh-, eighth-, and ninth-grade classes (N = 303) in May and June 2021. The confirmatory factor analysis and follow-up correlational analysis demonstrated various degrees of support for the dimensions of the Epistemic and Ontological Cognition Questionnaire, for the dimension of Value of Integration Information, and for the dimension of Historical Methodology in Generating Historical Knowledge. Reading comprehension correlated positively with epistemic belief dimensions related to epistemic criteria of justification by multiple sources, the value of integration information, and historical methodology. Academic achievement in the form of the end-of-grade marks obtained in the subjects of history and Czech language did not show a consistent relationship with the epistemic beliefs. The potential practical and research uses of the self-report questionnaires that were investigated in regular classroom instructions are discussed. The presented study aimed to explore the domain of history that witnessed ontological changes in students' reasoning since the 50's (Committee on the Study of History, 1969),  that gave rise to more systematic empirical studies on epistemology about history knowledge. In the 21st century, Maggioni and her colleagues (2004, 2009) constructed their self-reported questionnaire on epistemic stances on history knowledge. Ever since, following researchers further modified, advanced, and developed new measurement tools to identify student epistemic beliefs in history. Ontological theories (Kuhn et al., 2000) posited the epistemic development in college population, however, the new evidence demonstrated rudiments of epistemic reasoning in even younger population and presented its nonlinear growth (VanSledright & Reddy, 2014) contingent upon the characteristics of the learning domains (ill-structured x well-structured; Frederiksen, 1984). Since history can be viewed as an ill-structured domain, there is more room for learners to express and exchange their higher levels of epistemic beliefs compared to domains that belong among hard sciences (Barzilai & Weinstock, 2015; Kuhn & Weinstock, 2002). Therefore, history classrooms present an excellent opportunity for investigating epistemological stances of students in lower secondary education. The current study investigated the potential of epistemic beliefs measurement among the Czech history classrooms. The researchers selected assessment self-report questionnaires in the sample of students from western countries ranging from middle schools to college in the history domain (Greene et al., 2010; Stoel et al., 2017; Wiley et al., 2020). In the first step, the inspected measures were back-translated (Klassen et al., 2009) and refined by iterative sets of cognitive interviews 9/2020-5/2021 (Karabenick et al., 2007). The finalized sets of items were administered in the 7th, 8th, and 9th grade classrooms (N = 303) 5-6/2021. The confirmatory factor analysis and follow up correlational analysis demonstrated the support for the dimensions of Epistemic and Ontological Cognition Questionnaire (Greene et al, 2010), for the dimension on Value of Integration information (Wiley et al., 2020),  and for the dimension focusing on Historical Methodology in generating historical knowledge (Stoel et al., 2017). The student reading comprehension was correlated to epistemic belief dimensions related to epistemic criteria of justification by multiple sources. The potential practical and research uses of the investigated self-report questionnaires in regular history classroom instructions were discussed.